2021
DOI: 10.1080/10962247.2020.1823525
|View full text |Cite
|
Sign up to set email alerts
|

Residential cooking and use of kitchen ventilation: The impact on exposure

Abstract: Cooking is one of the most significant indoor sources of particles. This study investigated residential cooking and kitchen ventilation behaviors in Canadian homes, using data from 132 households in Halifax and Edmonton. Only 27% of the cooking activities were conducted with added ventilation (range hood use 10%, window opening 15%, and both 2%). The use pattern of the range hood was associated with mealtime and cooking method/device. The frequency of window opening was influenced by season and did not show a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…In fact, some kitchens have “ductless” hoods that recirculate fumes through activated charcoal filters, which are generally less effective at cleaning the air . Vented hoods have a range of effectiveness and function best when overhanging the stove. , Because exhaust hoods are separate from the stove and must be operated manually, vented hoods in practice are used only 25–40% of the time. …”
Section: Introductionmentioning
confidence: 99%
“…In fact, some kitchens have “ductless” hoods that recirculate fumes through activated charcoal filters, which are generally less effective at cleaning the air . Vented hoods have a range of effectiveness and function best when overhanging the stove. , Because exhaust hoods are separate from the stove and must be operated manually, vented hoods in practice are used only 25–40% of the time. …”
Section: Introductionmentioning
confidence: 99%
“…Similar to our study, a previous study found that kitchen ventilation was related to decrease the risk of the incident lung cancer, diabetes, and chronic obstructive pulmonary [43][44][45] This may be explained by that kitchen ventilation can reduce the concentrations of HAP from incomplete combustion of solid fuel and cooking oil fumes. 46 A previous study also suggested that kitchen exhaust fans/hoods were related to a low level of PAHs concentrations in the human body. 44 It was interesting to note that cooking with clean fuel and kitchen ventilation for a short time (<1.5 h/day) was associated with low prevalent depressive symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…Occupant health in buildings depends on the type of building under study. For example, residential cooking is considered one of the most substantial sources of indoor air pollutants in households, exposing occupants to fine air particles that can lead to respiratory problems [ 20 ]. In office spaces, the goal remains to establish a more comfortable, productive, and healthier work environment for office workers who spend most of their time sitting.…”
Section: Introductionmentioning
confidence: 99%